Cardiovascular magnetic resonance characterisation of myocardial involvement in tuberculous pericardial constriction with and without HIV co-infection - Palkowski, Gregori H (Department of Medicine, 2017)
Background:Tuberculous pericarditis includes the spectrum of pericarditis caused by Mycobacterium tuberculosis manifesting with pericardial effusion, cardiac tamponade, effusive-constrictive and constrictive pericarditis. In patients with pericardial tuberculosis, co-infection with human immunodeficiency virus (HIV) is associated with increased incidence of haemodynamic instability, electrocardiographic (ECG) ST elevation and mortality, suggesting an aggressive myopericarditis. However, little is known about myocardial involvement in patients with pericardial tuberculosis. Cardiovascular magnetic resonance (CMR) can assess non-invasively cardiac function, myocardial oedema, inflammation and fibrosis. Objectives: To assess cardiac and pericardial structure and function in patients with TBPC with and without HIV co-infection and to assess the relationship of left ventricular (LV) function with other imaging biomarkers. Methods: 72 patients with TBPC (37 male (51.3%), mean age 40 ± 14.3) were included in the study. Of these, 35 were HIV infected (17 male (48.6%), mean age 34 ± 8) and 37 were HIV uninfected (20 male (54.1%), mean age 51 ± 16). Assessments included clinical examination, ECG, echocardiography, serum and pericardial biomarkers and CMR (biventricular volumes and function, oedema, and late gadolinium enhancement - LGE). Results: HIV infected TBPC patients were younger (p<0.001), had lower serum haemoglobin (p<0.001) and were more likely to have NYHA class III and IV symptoms (p<0.001). There were no differences on ECG and echocardiography between HIV infected and uninfected TBPC patients. There were also no differences in global systolic function between HIV infected and uninfected TBP patients. Focal fibrosis on LGE was found more commonly in those with HIV infection (p<0.001). Pericardial effusions were frequent (>50%) in both groups of TBPC patients. Determinants of LV ejection fraction in TBPC included heart rate, LV size, E/A ratio, pericardial LGE and pericardial thickness (all p<0.01). Conclusions: HIV co-infection is associated with increased focal myocardial fibrosis in TBPC patients suggesting increased myocardial inflammation in those with HIV co-infection. In the future, it will be important to assess the prognostic significance of these findings.